On the collective monograph “Ethnonational processes in the Arctic: trends, problems, and prospects” - Vladimir M. Kapitsyn; Alexander E. Shaparov; Valery I. Kovalenko; Arbakhan K. Magomedov (Арктика и Север, 2019)
The article represents the review of the collective monograph “Ethnonational processes in the Arctic: trends, problems, and prospects.” The monograph is an original joint work of researchers at Russian research centers specializing in the study of the Arctic. The researchers focus on ethnonational processes in the context of the socio-economic, socio-political, legal, socio-cultural development of the Arctic territories of Russia. The interdisciplinary nature of the research, the full coverage of ethnonational policies and subregions, the depth of the study, the visualization of the material with tables, charts, graphs, maps determines not only the academic but also the comprehensive nature of the monograph under review.